Pendampingan berkelanjutan dalam membangun budaya mutu pembelajaran pada Guru MI - Nurhaningtyas Agustin; Akhmad Aji Pradana; Nurlaili Dina Hafni; Irfai Alfian Mubaidilla; Shohibul Asrofin (Nur Science Institute, 2026)
Learning quality culture is one of the key factors in improving the quality of education in madrasahs. However, the implementation of a quality culture at the Madrasah Ibtidaiyah (Islamic elementary school) level still faces several challenges, including the low quality of learning tools, limited reflective teaching practices, and the lack of sustainable learning evaluation. This community service program aimed to enhance teachers’ competencies in developing a learning quality culture through a sustainable mentoring program at MI P2A Gaji Kerek Tuban. The program employed a participatory approach, experiential learning, and the Plan-Do-Check-Act (PDCA) quality cycle. The activities were conducted through several stages, including program socialization, development of teaching materials, review of learning tools, classroom implementation, classroom observation, reflection and consultation, and reporting. The results indicated an improvement in teachers’ understanding of learning quality culture, an enhanced ability to develop learning tools, and the establishment of reflective and evaluative teaching practices. Furthermore, teachers successfully developed more systematic teaching modules, learning materials, and assessment instruments tailored to students’ needs. The program contributed to strengthening the learning quality culture and promoting continuous improvement in instructional practices.